The Law on Marrying Off Children Out of Wedlock by Their Biological Father According to Imam Syafi'i - Salsabillah, Alya; Khairunnisa, Dwi; Dwi Anggraini, Putri; Bastian, Adol (Samara: Journal of Islamic Law and Family Studies, 2025)
In recent times, there have been many cases of biological fathers marrying off their daughters outside of marriage, one of the factors being that the girl's parents did not disclose that she was born out of wedlock (adultery). The objective of this study is to examine the ruling on a biological father marrying off his daughter outside of marriage according to Imam Syafi'i. Imam Syafi'i opines that the marriage of a daughter by her biological father is invalid. This research employs a qualitative method with a library research (literature review) approach. Data were collected through the analysis of primary and secondary sources related to Islamic jurisprudence, particularly the views of Imam Syafi’i. The study aims to understand the legal and theological reasoning behind Imam Syafi’i’s opinion, by critically examining classical and contemporary scholarly works.